Сутність освітньої діяльності закладів вищої освіти зі специфічними умовами навчання як об’єкту нагляду (контролю) - Яценко, Ф. П.; Yatsenko, F. P. (Європейські перспективи. - 2023. - № 2. - С. 172-177, 2023)
З’ясовано сутність освітньої діяльності закладів вищої освіти зі специфічними умовами навчання як об’єкту нагляду (контролю). Визначено поняття «освіта», розкрито теоретичні підходи щодо тлумачення терміну «освітня діяльність». Доведено, що сутність освітньої діяльності закладів вищої освіти зі специфічними умовами навчання як об’єкту нагляду (контролю) полягає у здійсненні організації, забезпечення та реалізації науково-методологічних та інших практик, спрямованих на комплексний розвиток особистості курсантів (слухачів, студентів), ад’юнктів, які оволодівають достатнім обсягом компетентностей, необхідних для подальшої служби на посадах середнього та вищого складу в правоохоронних органах, з метою задоволення потреб Міністерства внутрішніх справ України, а також підпорядкованих йому центральних органів виконавчої влади, діяльність яких спрямована на реалізацію правоохоронної функції держави.

It was found that the educational activity of institutions of higher education with specific learning conditions as an object of supervision (control) includes many diverse elements, in particular: organizational, scientific-methodical, pedagogical and others, which in their entirety are aimed at achieving the main goal the existence and functioning of such ZVO. It has been proven that the essence of the educational activity of higher education institutions with specific learning conditions as an object of supervision (control) consists in the organization, provision and implementation of scientificmethodological and other practices aimed at the comprehensive development of the personality of cadets (students, students), etc. cadets who master a sufficient amount of competences necessary for further service in positions of middle and senior staff in law enforcement agencies, in order to meet the needs of the Ministry of Internal Affairs of Ukraine, as well as subordinate central bodies of executive power, whose activities are aimed at the implementation of the law enforcement function of the state. It is substantiated that the content of educational activities of higher education institutions with specific learning conditions as an object of supervision (control) is revealed in the following: aimed at comprehensive training of cadets (students, students), adjuncts, formation of their personal and professional qualities, mastery of competencies , which are sufficient for further service in the relevant central bodies of the executive power; its implementation involves the use of a number of financial, material, technical and human resources, checking the rationality and effectiveness of their use requires control (supervision); is implemented by specially authorized entities, whose activities are regulated not only by the norms of the legislation on higher education, but also by legal acts regulating the activities of the Ministry of Internal Affairs of Ukraine, to which the relevant higher education institutions are subordinate.

Выяснена сущность образовательной деятельности учреждений высшего образования со специфическими условиями обучения как объекта надзора (контроля). Определено понятие «образование», раскрыты теоретические подходы к толкованию термина «образовательная деятельность». Подчеркнуто, что образовательная деятельность заведений высшего образования со специфическими условиями обучения как объект надзора (контроля) включает в себя много разноплановых элементов, в частности: организационных, научно-методических, педагогических и других, которые в своей совокупности направлены на достижение основной цели существования и функционирования таких учреждений высшего образования.
Keywords: освіта; education; образование; освітня діяльність; educational activity; образовательная деятельность; заклади вищої освіти зі специфічними умовами навчання; institutions of higher education with specific study conditions; заведения высшего образования со специфическими условиями обучения; нагляд; supervision; надзор; контроль; control